Survival and Success of ITI Implants and Prostheses: Retrospective Study of Cases with 5-Year Follow-Up - Gokcen-Rohlig, Bilge; Yaltirik, Mehmet; Ozer, Senem; Tuncer, Ebru Demet; Evlioglu, Gulumser (European Journal of Dentistry, 2009)
Objectives: The use of osseointegrated implants as an endoestal anchorage device to provide support for dental prostheses is a reliable and widely accepted treatment modality. The purpose of this study was to evaluate the clinical performance of non-submerged implants placed in the maxilla or in the mandible.Methods: A total of 146 International Team for Implantology (ITI) (Straumann AG, Waldenburg, Switzerland) implants were placed in 42 patients (20 women, 22 men, mean age 42). The cases were examined retrospectively in order to evaluate the clinical efficiency of non-submerged ITI implants and to determine the success rate of implant retained/supported prosthesis after a 5-year period. All implants were assessed clinically and radiographically on a yearly basis.Results: The 5-year cumulative success rates for maxillary and mandibular implants were 91.00% and 97.81%, respectively. The most common prosthetic complication was abutment accompanied by screw loosing (3.42%). Veneering material fracture was documented in only one patient.Conclusions: Within the limitations of the observation period and sample number, the present findings confirmed sufficient success and survival rates of ITI implants placed in mandible as well as implants placed in the maxilla after a 5-year period. (Eur J Dent 2009;3:42-49)
Keywords: Cumulative success rate; Maxillary implants; Mandibular implants; Dental prosthesis